2019
DOI: 10.4236/ojf.2019.93010
|View full text |Cite
|
Sign up to set email alerts
|

Using Biophysical Variables and Stand Density to Estimate Growth and Yield of <i>Pinus patula</i> in Antioquia, Colombia

Abstract: Timberland investment opportunities in Colombia are expected to increase as a result of the peace agreement recently signed between the Colombian government and the Revolutionary Armed Forces of Colombia. This new socio-political environment may facilitate the expansion of commercial forest plantations on a wider range of site conditions that are currently considered in existing biometric tools. Data from 1119 temporary plots of unthinned, unmanaged, and genetically unimproved Pinus patula plantations in the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 42 publications
1
5
0
2
Order By: Relevance
“…Factors from 0.7 to 1.3 were applied to both costs and incomes, and the LEV and IRR variations, ceteris paribus, were assessed. The 95% prediction interval of the volume estimates is within +/-30% of the mean yield curve (Restrepo et al, 2019). Besides, although the volatility in the timber market in Colombia has not been assessed, other authors have found volatility of ~23% for more mature markets (Restrepo et al, 2020).…”
Section: Financial Analysismentioning
confidence: 76%
See 2 more Smart Citations
“…Factors from 0.7 to 1.3 were applied to both costs and incomes, and the LEV and IRR variations, ceteris paribus, were assessed. The 95% prediction interval of the volume estimates is within +/-30% of the mean yield curve (Restrepo et al, 2019). Besides, although the volatility in the timber market in Colombia has not been assessed, other authors have found volatility of ~23% for more mature markets (Restrepo et al, 2020).…”
Section: Financial Analysismentioning
confidence: 76%
“…The parameter ϕ is estimated as a linear function of an intercept, and soil pH (a dummy variable that equals one if pH is in the range 5.1-6, and zero if pH is in the range 4.1-5), slope (S, degrees), and stand density (N, trees per hectare) (Equation 2). The parameter β was estimated as a linear function of an intercept, and the mean annual temperature (T e , °C) by the mean annual precipitation (P r , mm) ratio (T e P r ) (Brown and Lugo, 1982;Restrepo et al, 2019).…”
Section: γ =mentioning
confidence: 99%
See 1 more Smart Citation
“…Los asteriscos indican la significancia de las correlaciones (* p<0.05; **p<0.01; *** p<0.001; ns p>0.05). Los árboles del Pacífico presentan una amplia variación en el CDA; se presentaron diferencias a nivel de localidades, categorías diamétricas y mecanismos nutricionales, lo cual es similar a lo reportado en estudios desarrollados en bosques tropicales que evidencian este tipo de variación (Turner, 2001;Toledo et al, 2011;Baribault et al, 2012), además de corroborar la influencia de factores como la calidad del sitio o condiciones ambientales, la edad del bosque y características intrinsecas como la genética, la densidad de individuos, los grupos taxonómico y ecológico, entre otros, que tienen incidencia aunque no se evaluaron (Russo et al, 2005;Restrepo et al, 2019).…”
Section: Discussionunclassified
“…En bosques tropicales, aunque la mayoría de los árboles crecen muy lentamente (promedio 1.0 mm.año -1 ) (Turner, 2001;Baribault et al, 2012), presentan un rango amplio de variación: entre 0.5 y 6.0 mm.año -1 en diámetro, con una tasa máxima cercana a 15 mm.año -1 (Turner, 2001). En tal sentido, se ha planteado que el crecimiento de los árboles es una función de cuatro factores: 1) la edad del bosque, 2) la calidad del sitio o las condiciones ambientales, 3) las características intrínsecas como la genética, y 4) la densidad de individuos y las prácticas de manejo del bosque, incluyendo la fertilización, el manejo de plagas y el control de competencia por vegetación (Restrepo et al, 2019). Esto explica por qué en bosques tropicales primarios y secundarios se presenta un amplio rango de variación en el crecimiento.…”
Section: Introductionunclassified